2006
DOI: 10.1094/pd-90-1457a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Citrus exocortis viroid, Iresine viroid, and Tomato chlorotic dwarf viroid in New Ornamental Host Plants in India

Abstract: Columnea latent viroid, originating from ornamental plants, is known to be harmful to crop plants (2). Despite the potential threat to crop plants, the importance of ornamental plants in viroid evolution is not fully appreciated. Availability of a Pospiviroid genus-specific primer pair (1) to detect the most prevalent viroids in ornamental plants and a simplified nucleic acid preparation protocol (3) for use in reverse-transcription polymerase chain reaction (RT-PCR) have facilitated surveys of ornamental plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…# EU729744) and the USA (Ling et al 2009). In addition to the tomato crop, TCDVd has also been isolated from several greenhouse grown ornamental plants (e.g., Verbena x hybrida (Singh et al 2006a), Petunia x hybrida (Verhoeven et al 2007;James et al 2008), Brugmansia sanguinea (acc. # EF 626530) and Vinca minor (Singh and Dilworth 2008).…”
Section: Introductionmentioning
confidence: 99%
“…# EU729744) and the USA (Ling et al 2009). In addition to the tomato crop, TCDVd has also been isolated from several greenhouse grown ornamental plants (e.g., Verbena x hybrida (Singh et al 2006a), Petunia x hybrida (Verhoeven et al 2007;James et al 2008), Brugmansia sanguinea (acc. # EF 626530) and Vinca minor (Singh and Dilworth 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The finding of CEVd infection in seed-grown seedlings, in moss Verbena (Glandularia puchella; Singh et al 2006a) in India and Impatiens (Impatiens walleriana; unpublished observation) in Canada in 2006 pointed to the possibility of seed transmission of CEVd from Impatiens and Verbena seeds.…”
Section: Introductionmentioning
confidence: 97%
“…Recent surveys to determine the prevalence of pospiviroids in ornamental plants have shown that CEVd is carried symptomlessly in vegetativelypropagated plants of Impatiens and Verbena species (Bostan et al 2004;Nie et al 2005;Singh et al 2006a). The finding of CEVd infection in seed-grown seedlings, in moss Verbena (Glandularia puchella; Singh et al 2006a) in India and Impatiens (Impatiens walleriana; unpublished observation) in Canada in 2006 pointed to the possibility of seed transmission of CEVd from Impatiens and Verbena seeds.…”
Section: Introductionmentioning
confidence: 99%
“…바이로이드가 주로 감염되는 숙주로는 사과, 배, 포도, 토마 토, 감자, 시트러스, 국화, 코코넛 팜, 아보카도, 홉 등이 있다 [58]. 주로 야기되는 바이로이드는 Pospiviroidae과의 Apple scar skin viroid (ASSVd) [46], Pear blister canker viroid (PBCVd) [24], Citrus bent leaf viroid (CVd-Ib) [63], Citrus exocortis viroid (CEVd) [68], Hop stunt viroid (HSVd) [36], Coconut cadang-cadang viroid (CCCVd) [79], Potato spindle tuber viroid (PSDVd) [67], Coleus blumei viroid 1 (CbVd) [1], Avsunviroidae과의 Avocado sunblotch Viroid (ASVd) [10], Peach latent mosaic viroid (PLMVd) [29], Eggplant latent viroid (ELVd) [14] 등이 있다( Table 1).…”
unclassified